1996
DOI: 10.1074/jbc.271.9.5150
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Class 3 Aldehyde Dehydrogenase in Cultured Rat Corneal Epithelium

Abstract: Mammalian Class 3 aldehyde dehydrogenase (ALDH) is normally associated with neoplastic transformation or xenobiotic induction by aromatic hydrocarbons in liver. However, Class 3 ALDH is constitutively expressed at it's highest specific activity in corneal epithelium. Tissue-specific, differential gene expression is often controlled by alternative, independent molecular pathways. We report here the development of an in vitro corneal epithelium culture system that retains constitutive high expression of the ALDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[17,22,27] We used the A549 (ALDH1A1 and ALDH3A1 expressing), SF767 (ALDH3A1 expressing) and CCD-13Lu (ALDH non-expressing) cells to assess the overall cytotoxicity and ability of CB29 analogs to enhance the sensitivity of cyclophosphamide and its derivatives. [20,24] The ED 50 values for mafosfamide on A549 and SF767 cells were 125 μM and 150 μM, respectively, while primary cells, CCD-13Lu were more sensitive to mafosfamide with an ED 50 of 40 μM (Figure S2). CB29 as well as compounds 17, 2, 18, 19, 11, 8, 9 and 10 were chosen because they were selective toward ALDH3A1 and showed no inhibitory potential toward ALDH1A1, ALDH1A2, ALDH1A3, ALDH1B1 and ALDH2 activity in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,22,27] We used the A549 (ALDH1A1 and ALDH3A1 expressing), SF767 (ALDH3A1 expressing) and CCD-13Lu (ALDH non-expressing) cells to assess the overall cytotoxicity and ability of CB29 analogs to enhance the sensitivity of cyclophosphamide and its derivatives. [20,24] The ED 50 values for mafosfamide on A549 and SF767 cells were 125 μM and 150 μM, respectively, while primary cells, CCD-13Lu were more sensitive to mafosfamide with an ED 50 of 40 μM (Figure S2). CB29 as well as compounds 17, 2, 18, 19, 11, 8, 9 and 10 were chosen because they were selective toward ALDH3A1 and showed no inhibitory potential toward ALDH1A1, ALDH1A2, ALDH1A3, ALDH1B1 and ALDH2 activity in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…[20,21,22,23] It is also expressed in some normal human tissues such as cornea and keratinocytes. [18,24] Despite being present in normal cells, studies have shown that Aldh3a1(-/-) knockout mice are viable. [25] High ALDH3A1 activity in normal cells protects these cells from the products of lipid peroxidation, [26] but can lead to drug resistance in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Discarded limbal rims from corneal transplants or eye banks are often a source for primary human corneal epithelial cells (de Paiva et al, 2005; Kahn et al, 1993; Kim et al, 2012; Nakamura et al, 2004). Rabbit (Cha et al, 2004; Fini and Girard, 1990), rat (Boesch et al, 1996; Marshall and Hanrahan, 1991), and mouse (Kawakita et al, 2004; Li et al, 2010) primary corneal epithelial cells have also been generated and used successfully. Due to its small size, it is more difficult to generate primary corneal epithelial cells from the mouse.…”
Section: Ex Vivo Experimental Optionsmentioning
confidence: 99%
“…157 The nonspecific ALDHs are further classified into numerous subclasses based on their conserved nucleic acid sequences and are known as Class 1, Class 2 and Class 3 ALDHs, based on cell-specific expression and sequence identity. 158 3E1. Class 1 aldehyde dehydrogenases (ALDH1).…”
Section: E Aldehyde Dehydrogenases (Aldhs)mentioning
confidence: 99%
“…164,177 Also, ALDH3 has been shown to metabolize aldehydes formed during lipid peroxidation. 163 The high constitutive expression of ALDH3A1 in the corneal epithelium, 20-40% of the total water-soluble protein in mammalian corneal epithelium, 158 perhaps serves as protection against volatile aldehydes and/or may be associated with the detoxification of medium-chain aldehydes produced during UV-induced lipid peroxidation by acting as a UV-sink via binding NAD + and absorbing UV light. 178 Very low levels of ALDH3 activity are detectable in normal mammalian liver, but high levels of both hepatic ALDH3 transcript and enzyme activity are obtained after exposure to certain xenobiotics such as PAHs, 3-methylcholanthrene, or dioxins, including TCDD.…”
Section: E Aldehyde Dehydrogenases (Aldhs)mentioning
confidence: 99%